Which intervention is more effective in improving sarcopenia in older adults? A systematic review with meta-analysis of randomized controlled trials. (March 2023) - Park, Seong-Hi; Roh, Younhee
Abstract: This systematic review aims, however, to determine which intervention is more effective. The skeletal muscle index (SMI), handgrip, and gait speed were used as indicators of improvement, and these effects were compared across six subgroups: combined intervention versus exercise; nutrition or control group; exercise versus nutrition; and exercise or nutrition versus control group. Out of 1596 articles, 32 studies (3063 older adults) were selected and meta-analyzed. Comparing the combined intervention with a control group, the WMD was 0.20 kg/m 2, 1.56 kg, and 0.08 m/s for SMI, handgrip, and gait speed, respectively, all of which showed a statistically significant improvement. When a combined intervention was compared with exercise and nutrition, the former resulted in improvements in handgrip (WMD 0.38 kg) and gait speed (WMD 0.12 m/s). On comparing exercise and nutrition, there was an improvement in gait speed (0.12 m/s) with exercise alone. On comparing exercise with a control group, only handgrip (WMD 1.74 kg) and gait speed (WMD 0.11 m/s) showed improvement, whereas in the nutrition versus the control group, only the handgrip (WMD 0.90 kg) improved. Although exercise and nutritional therapy together demonstrated improved muscle strength, exercise is recommended for the improvement of physical performance. Highlights: A loss of muscle mass and strength is a part of the aging process, but it is a disease called sarcopenia. Currently, the only intervention of exercise and nutrition can improve sarcopenia. Combined interventions with exercise and nutrition demonstrated all improvements in muscle quality, strength, and physical performance. Exercise and nutrition improve both muscle strength, but exercise can also enhance physical performance.